Generation and immunity effect evaluation of biotechnology-derived Aeromonas veronii ghost by PhiX174 gene E-mediated inactivation in koi (Cyprinus carprio koi). Issue 86 (March 2019) - Jiang, Na; Luo, Lin; Xing, Wei; Li, Tieliang; Yuan, Ding; Xu, Guanling; Li, Wentong; Ma, Zhihong; Jin, Liangyun; Ji, Man
Abstract: Aeromonas veronii is a conditional pathogen causing high mortality in many freshwater fish species worldwide. Bacterial ghosts are nonliving Gram-negative bacteria devoid of cytoplasmic contents, which induce protective immunity against microbial pathogens. The aims of this study were: a) to produce A. veronii ghost (AVG) constructed by PhiX174 gene E ; b) to evaluate the specific, non-specific immune effects and protective immunity of AVG against A. veronii in koi. The lysis plasmid pBBR-E was constructed by cloning PhiX174 gene E into the broad-host-range vector pBBR1MCS2, and then transformed into A. veronii 7231. AVG was generated by increasing the incubation temperature up to 42 °C. Lysis of A. veronii occurred 3 h after temperature induction and completed in 12 h. The efficiency of ghost induction was 99.9998 ± 0.0002%. Koi were immunized intraperitoneally with AVG, formalin-killed bacteria (FKC) or phosphate buffered saline (PBS) respectively, and then respiratory burst (RB), myeloperoxidase (MPO), lysozyme (LZM), malondialdehyde (MDA), complement 3 (C3) and antibody activities were examined in serum. Compared with negative control of PBS, the RB, MPO, LZM activities were significantly higher in koi immunized with AVG (P < 0.05). Nevertheless, the MDA activities of AVG treatment were significantly lower than those of PBS treatment (P < 0.05). The serum agglutination titers and IgM antibody titers in AVG group were significantly higher than those in FKC or PBS groups. After challenged with the parent strain A . veronii 7231, the average mortality of AVG group was significantly lower than that of FKC and PBS groups (P < 0.05) and the relative percent survival (RPS) of AVG group (73.92%) was higher than that of FKC group (43.48%). Therefore, AVG have the potential to induce protective immunity and they may be ideal vaccine candidates against A. veronii in koi. Highlights: A. veronii ghosts (AVG) were successfully generated by the temperature-controlled expression of the PhiX174 lysis gene E. The efficiency of AVG generation was 99.9998 ± 0.0002%. It was better than other reported ghosts. AVG had the structural integrity of bacterial outer membrane except for the lysis pore. Compared with PBS, the RB, MPO, LZM activities were significantly higher immunized with AVG. The serum agglutination titers and IgM antibody titers in AVG group were significantly higher than those in FKC or PBS groups. The RPS of AVG group was higher than that of FKC group. AVG provided strong protection for koi.